The Uniersal and the Particular: Twin Foci in Holocaust Education - Brown, Michael (Wydawnictwo Naukowe UAM w Poznaniu; Wydawnictwo PWSFTViT w Łodzi, 2011)
The Holocaust has pedagogical signicance not only for Jews and for Israel, but perhaps even more so for Christians, Europeans, North Americans, nad others. Its ramifications are especially salient with regard to theology and notions of nationality nad ethnicity. Examples are given from historical and liturgical texts, as well as belles lettres.
Keywords: Universal; Particular; Holocaust Education; Christianity; Judaism; Israel; Poland; Germany; Theology